Superconducting single-photon detector with a system efficiency of 93% operated in a 2.4 K space-application-compatible cryocooler. (19th May 2021) - Hu, Peng; Ma, Yuexue; Li, Hao; Liu, Ziyao; Yu, Huiqin; Quan, Jia; Xiao, You; You, Lixing; Liu, Yanjie; Liang, Jingtao; Wang, Zhen
Abstract: We report herein the development of a superconducting nanowire single-photon detector (SNSPD) that uses a hybrid cryocooler compatible with space applications. The hybrid cryocooler incorporates a two-stage high-frequency pulse-tube cryocooler and a Joule–Thomson loop, which produces a minimum temperature of 2.2 K. The SNSPD with the structure of sandwiched nanowires integrated in the cryocooler shows a maximum detection efficiency of 93% at 1550 nm, which makes it promising for deep-space communications and quantum information applications.